Clinical Efficacy of Short-Term Peripheral Nerve Stimulation in Management of Facial Pain Associated With Herpes Zoster Ophthalmicus - Han, Rui; Guo, Gangwen; Ni, Yuncheng; Wang, Ziyang; Yang, Liuqing; Zhang, Jianping; Li, Xuelian; Hu, Rong; Huang, Dong; Zhou, Haocheng (Frontiers in Neuroscience, 2020)
Objective: Peripheral nerve stimulation may be an alternative option to treat severe facial pain. The aim of this study is to assess the application of peripheral nerve stimulation for pain management in patients with herpes zoster ophthalmicus. Method: Retrospective analysis was performed in patients suffered severe facial pain caused by ophthalmic herpetic lesion, to identify the change of pain degree before and after peripheral nerve stimulation therapy up to 12 months. Results: 18 patients were enrolled for analysis, with mean age at 70.8±9.5 years old. 15 patients presented sub-acute pain for 1-3 months, and three patients suffered postherpetic neuralgia. Dramatic pain relief was achieved in 83% patients (15/18) upon initial removal of stimulator, with over 50% pain reduction. The long-term analgesic effect was reported at 6- and 12-month follow-up, with 4.7 (n=18) and 5.2 (n=12) pain scores decreased respectively. The incidence of postherpetic neuralgia was 7% (1/15) at 6 months in sub-acute pain group. No obvious adverse effect was observed. Conclusions: Peripheral nerve stimulation treatment may be an effective and safe approach for pain control in patients with herpes zoster ophthalmicus.